The Neuroscience of Organizational Trust and Business Performance: Findings From United States Working Adults and an Intervention at an Online Retailer - Johannsen, Rebecca; Zak, Paul J. (Frontiers in Psychology, 2021)
This paper reports findings from a nationally-representative sample of working adults to quantify how a culture trust improves business performance. Analysis of the national sample showed that organizational trust and alignment with the company's purpose are associated with higher employee incomes, longer job tenure, greater job satisfaction, less chronic stress, improved satisfaction with life, and higher productivity. Employees working the highest quartile of organizational trust had average incomes 10.3% higher those working in the middle quartile of trust (p=0.000) indicating that trust increases productivity. In order to demonstrate the causal effect of trust on business performance, we created an intervention to increase organizational trust in a division facing high job turnover at a large online retailer. The intervention increased organizational trust by 6% and this improved job retention by 1%. These studies show that management practices that increase organizational trust have salubrious effects on business performance.